Model Pembelajaran Project Based Learning (PJBL) untuk Mengembangkan Kreatifitas Siswa Sekolah Dasar - Inayah, Seni Siti; Marginingsih, Ria (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
This service activity is carried out to improve and develop the creativity of 5th grade elementary school students at SDN 2 Handapherang. Online learning during the pandemic is enough to make students bored and limited in their efforts to develop themselves. Through the Project Based Learning (PJBL) learning model, it is hoped that it can spur students to think creatively in solving a problem. The activities carried out of course refer to the syntax of the Project Based Learning (PJBL) learning model, namely presenting problems, making plans & arranging schedules, monitoring project creation, assessment and evaluation. From the results of the program that has been carried out students are able to solve problems with different styles. This means that each student has his or her own way of determining a solution to the given problem. The assessment is carried out by taking into account the aspects of fluency, novelty and flexibility.